Low-Cost Tissue Oximetry Using Discrete Light-Emitting Diodes - Panula, Tuukka; Mustajoki, Inka; Karhinoja Katri; Kjellman Maria; Sirkiä Jukka-Pekka; Kaisti, Matti (United States, 2026)
Tissue oxygen saturation $(\text{StO}_{2})$ is an important biomarker used to monitor patients after a surgical intervention. $\text{StO}_{2}$ is often measured using various techniques that require expensive, bulky, and complicated instrumentation. We propose a low-cost instrument design to measure $\text{StO}_{2}$ level using discrete light-emitting diodes (LED) and a photodiode receiver. The instrument was tested using a liquid tissue phantom to verify the operation of the system in vitro during hemoglobin deoxygenation. A commercial spectrometer was used as a reference device. Furthermore, we tested the device in vivo by measuring skin $\text{StO}_{2}$ during a brachial artery occlusion test. The results of these experiments suggest that the device is capable of measuring $\text{StO}_{2}$ with sufficient accuracy and could provide a low-cost alternative to spectrometer-based tissue oximetry in clinical use.
2024 IEEE International Instrumentation and Measurement Technology Conference (I2MTC) : Conference Proceedings